Accumulation of Cd in the early stages of the development of rainbow trout Oncorhynchus mykiss Exposed to Cd-based quantum dots and Cd salt - Cibulskaitė, Živilė; Kazlauskienė, Nijolė; Jokšas, Kęstutis; Kulvietis, Vytautas; Makaras, Tomas; Montvydienė, Danguolė; Stankevičius, Mantas; Rotomskis, Ričardas (International Conference “Environmental Engineering”, 2017)
The main aims of the present study were: 1) to determine the concentration of Cd in water during the experiment after longterm exposure to rainbow trout embryos and larvae to sublethal concentrations of Cdbased quantum dots (QDs) and Cd chloride salt, and 2) to evaluate accumulation of Cd in the whole body of testorganisms depending on the type of chemical substances (QDs or single Cd) and the duration of exposure. Experimental studies at the early developmental stages of rainbow trout were performed under static conditions. Cd concentration in water during the experiment was significantly higher in QD solution than in CdCl2 solution, and it declined over time. A comparative analysis indicated that the Cd accumulation in test organisms from QDs was mostly higher than that from CdCl2. The accumulation of Cd from QDs tends to increase with increasing duration of exposure. The bioconcentration factor for Cd increased in embryos and larvae over time until reaching the maximum at the end of the QD exposition.